Measurement of polarization observables in elastic and inelastic electron-deuteron scattering at the VEPP-3 storage ring; Nuclear Physics A; Vol. 684, № 1 - Nikolenko D. M.; Arenhovel H.; Barkov L. M.; Belostotsky S. L.; Dmitriev V. F.; Dyug M.V.; Gilman R.; Holt R. J.; Isaeva L. G.; de Jager C. W.; Kinney E. R.; Kowalczyk R. S.; et al. (2001, 2001)
В фонде НТБ ТПУ отсутствует